Financial factors affecting earnings management and earnings quality: New evidence from an emerging market - Isam Saleh; Malik Abu Afifa; Fadi Haniah (ACRN Journal of Finance and Risk Perspectives (JOFRP), 2020)
The purpose of this study is to examine the effect of financial factors on earnings management and earnings quality. Moreover, the study examines the role of earnings management as a mediator in the effect of the financial factors on earnings quality. It provides some empirical evidences from an emerging market, especially from the Jordanian market. The study uses a panel data analysis method over a ten-year period (2009-2018). The study population includes all Jordanian insurance companies listed in Jordanian market at the end of the year 2019, and the study sample consists of 20 Jordanian insurance companies (a complete population), giving a total of 200 observations for each variable. The results indicate that all financial factors in the model combined affect the earnings management and earnings quality. In addition, earnings management negatively affects earnings quality, and earnings management fully mediates the effect of financial factors on earnings quality. The study advises that policy makers ought to follow good legislation to curb the company's earnings management activities. Hence, the policy makers need to apply regulations which enrich the company's effectiveness and efficiency whilst protecting the investors and other interested parties from risk.
Keywords: M21; M41; G30; 330; Financial factors; Earnings manipulation; Reporting quality; Financial information quality; Jordanian market